2008
DOI: 10.1200/jop.0832001
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Dosing Strategies in the Obese, Elderly, and Thin Patient: Results of a Nationwide Survey

Abstract: Purpose: Determining the optimal starting dose of chemotherapy (CHT) presents a considerable challenge when using bodysurface area (BSA)-based dosing, particularly in obese, elderly, or thin patients. We sought to document the range of approaches employed when administering CHT to these patients. Methods Conclusion:This analysis of BSA-based CHT dosing methods demonstrates significant variability in practice. Based on evidence from adjuvant studies showing that actual BSA-based dosing is desirable, a substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 40 publications
0
54
0
2
Order By: Relevance
“…Given the delicate balance between efficacy and toxicity, numerous studies evaluating dose-capping and dose-adjustment practices have indicated that they may compromise outcomes in obese patients receiving chemotherapy. 2,4,5 Recognizing the problems that the extremes of body size incur, the American Society of Clinical Oncology published a clinical practice guideline supporting the use of actual body weight when calculating doses for most chemotherapy agents. 6 However, these recommendations were based on results from studies conducted in solid tumor malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Given the delicate balance between efficacy and toxicity, numerous studies evaluating dose-capping and dose-adjustment practices have indicated that they may compromise outcomes in obese patients receiving chemotherapy. 2,4,5 Recognizing the problems that the extremes of body size incur, the American Society of Clinical Oncology published a clinical practice guideline supporting the use of actual body weight when calculating doses for most chemotherapy agents. 6 However, these recommendations were based on results from studies conducted in solid tumor malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obese patients have historically been capped at a BSA of 2.0 m 2 , and the elderly are often treated at reduced dosages empirically. Concerns about overdosing obese cancer patients using actual body weight are largely unfounded, and with modern supportive care, most elderly patients with cancer can tolerate standard dosages of chemotherapy [23][24][25]. The occurrence of C-iN in these two groups may correlate with outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Para esquemas de QT habitualmente usados en el tratamiento de CCR, pulmón, ginecológicos o CM, no se ha demostrado mayor toxicidad cuando la dosis es calculada en base a la SC real, incluso si esta es mayor a 2; sin embargo, debido al temor a toxicidades no deseadas, es frecuente el cálculo de dosis según "peso ideal" o hasta un máximo de SC de 2,2 [45][46][47] . La reducción de dosis podría comprometer la eficacia del tratamiento.…”
Section: Quimioterapia (Qt)unclassified